The need for self-education as the driving force of sustainable professional development of future English Language teachers - Shymanovych, Iryna (Запоріжжя: КПУ, 2021)
The article deals with the issue of the need for self-education in the context of teacher training. In a rapidly changing world there is a great demand for teachers who are strongly motivated and interested in their professional development. It is stated that any good pre-service training cannot prepare teachers to the challenges in their profession. The focus of this study is on the need for self-education as a source of selfactualization and professional growth. The main purpose of this work is to highlight the importance of teacher development and define basic conditions that help to form future English teachers’ need for self-education as the driving force of their sustainable professional development.
Потреба у професійному самовихованні як рушійна сила професійного розвитку майбутнього вчителя англійської мови
Keywords: Need for self-education; teacher training; future English language teacher; professional development; self-study